PENGEMBANGAN SPIRITUALITAS KRISTEN PESERTA DIDIK MELALUI PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN BERBASIS TEOLOGI KONTEKSTUAL - Delima Agista Konda; Vivi vaulya laminatara Sirante; Kalarce Abidondifu; Satriani Andi Paembonan; Binson Toni (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This article discusses the development of students' spirituality through contextual theology-based Christian Religious Education (PAK) learning as a pedagogical approach relevant to the dynamics of modern life. Contextual theology is understood as an effort to integrate Christian faith teachings with students' life experiences, culture, and social realities, so that learning is not only cognitive but also transformative. The study used a descriptive qualitative method with data collection techniques such as interviews, observation, and document analysis, which were then analyzed through the stages of data reduction, data presentation, and conclusion drawing.